A terbium rich orthoborate LiSrTb2(BO3)3 and its analogues. (1st October 2015) - Chen, Pengyun; Xia, Mingjun; Li, R. K.
Abstract : A terbium rich orthoborate, LiSrTb2 (BO3 )3, shows paramagnetic behavior, and up to 21 isomorphic analogues have been prepared. Abstract : A terbium rich orthoborate, LiSrTb2 (BO3 )3, has been successfully synthesized by a solid state reaction and crystallized from a high temperature flux. Single crystal X-ray diffraction results show that LiSrTb2 (BO3 )3 possesses the P 3̄ m 1 space group, with cell parameters of a = 10.3845(4) Å, c = 6.4739(8) Å, and Z = 3. In the structure, the terbium atom coordinates to eight oxygen atoms to yield a TbO8 polyhedron. These polyhedra are connected with each other to form a layer of trigonal [Tb3 O21 ] and hexagonal [Tb6 O33 ] blocks in the ab plane, and then the layers are further linked by the triangular BO3 groups along the c direction. The magnetic susceptibility measurements show that LiSrTb2 (BO3 )3 exhibits paramagnetic behaviors from 2 K to 300 K. The diffuse optical reflection spectrum indicates that LiSrTb2 (BO3 )3 is transparent in the range 500–1500 nm, and effective green emission is detected in the photoluminescence of LiSrTb2 (BO3 )3 . In addition, a series of isostructural lanthanide analogues LiSrLn2 (BO3 )3 (Ln = Pr, Nd, Sm–Lu) and LiBaLn2 (BO3 )3 (Ln = Pr, Nd, Sm–Tm) have also been prepared by solid state reactions.